Prevalence and Associated Factors of Diarrhea Among Under‐Five Children in Maraki Health Center, Gondar Zone, Amhara Region, Ethiopia: A Cross‐Sectional Study - Mequanente Dagnaw; Meera Indracanti (Health Science Reports, 2026)
ABSTRACT Background and Objective Diarrheal disease remains one of the leading causes of morbidity and mortality among under‐five children, particularly in low‐ and middle‐income countries. Despite ongoing efforts to improve water, sanitation, and hygiene (WASH) conditions, childhood diarrhea continues to be a major public health concern in Ethiopia. This study aimed to assess the prevalence of diarrhea and associated factors among under‐five children attending Maraki Health Center, Gondar Zone, Amhara Region, Ethiopia. Methods An institution‐based cross‐sectional study was conducted among 361 mothers or primary caregivers of under‐five children attending Maraki Health Center in 2024. Participants were selected using systematic random sampling. Data were collected through face‐to‐face interviews using a structured interviewer‐administered questionnaire. Data were coded, checked for completeness, entered into Epi Info version 7.2.7, and exported to SPSS version 25 for cleaning and analysis. Descriptive statistics were used to summarize participant characteristics and the prevalence of diarrhea. Bivariable and multivariable logistic regression analyses were performed to identify factors associated with childhood diarrhea. Variables with a p value < 0.25 in the bivariable analysis were entered into the multivariable model. Multicollinearity was assessed using the Variance Inflation Factor (VIF), and model fitness was evaluated using the Hosmer–Lemeshow goodness‐of‐fit test. Statistical significance was declared at p < 0.05, and adjusted odds ratios (AORs) with 95% confidence intervals (CIs) were used to measure the strength of associations. Results The prevalence of diarrhea among under‐five children during the 2 weeks preceding the survey was 28.8% (104/361; 95% CI: 24.1%–33.5%). Maternal illiteracy (AOR = 3.78, 95% CI: 1.44–9.87), maternal age of 18–25 years (AOR = 2.40, 95% CI: 1.60–3.80), rural residence (AOR = 3.90, 95% CI: 2.20–6.80), use of unimproved water sources (AOR = 3.90, 95% CI: 2.71–5.21), handwashing with water only (AOR = 1.80, 95% CI: 1.21–3.13), female sex of the child (AOR = 2.80, 95% CI: 1.45–4.12), and child age ≤ 11 months (AOR = 3.78, 95% CI: 1.44–5.87) were significantly associated with childhood diarrhea. Conclusion The prevalence of childhood diarrhea in the study area was high. Maternal education, maternal age, place of residence, source of drinking water, handwashing practices, child sex, and child age were significant predictors of diarrhea. Strengthening maternal health education, improving access to safe drinking water, and promoting proper handwashing practices, particularly among rural households, may help reduce the burden of childhood diarrhea among under‐five children.